Studi Literatur Pembiayaan Murabahah Pada Perbankan Syariah di Indonesia - Rizky Akbar Siregar; Fardan Ali Ali Torabora Siregar; Chairina Chairina (Faculty of Islamic Religion, Universitas Muhammadiyah Sumatera Utara, 2022)
Islamic banks are Islamic monetary establishments that act as brokers, specifically gathering finances from the general public withinside the shape of deposits and channeling them thru the monetary system. Murabaha is a manner of channeling finances to Islamic banks. Murabahah is promoting and shopping for items on the unique charge with an extra agreed earnings. The benefit of Murabaha is that the vendor should tell the purchaser of the acquisition charge of the product, indicating the quantity of earnings to be brought to the cost. Murabahah may be performed in methods specifically. purchase with orders and with out orders. The principal factor of this studies is to discover how murabaha financing is in Islamic banking in Indonesia. Various research have proven that the murabaha financing approach is a pinnacle precedence in lots of Islamic banks each in Indonesia and abroad.